(untitled) (Research, Society and Development, 2020)
The objective of the article was to present central ideas and understand aspects related to gamification in the learning process. It is justified by the need to carry out a survey of the materials already produced on the theme and its applicability in high school. A content analysis of the works already prepared by other researchers and which add or enrich the work proposed by us. As for the research problem, we sought to answer relevant aspects and practices of gamification used in the classroom, in high school. Two hundred and twenty-six works were found between the years 2013 and 2019. As for the methodology, it is a systematic review of the literature with analysis, developed from a survey in the databases of material consisting of published scientific articles. This will enable an assessment of the consistency and generalization of the results. The sample was selected according to its relevance in relation to the research objectives, using the terms gamification- gamification- teaching learning- educational games, classifying eight articles. Based on authors such as Fardo (2013), Fadel (2014), MC Gonigal (2014) and Moran (2013), it brings as a result the conclusion that the examined papers present as goals the applicability of gamification in high school, in the learning process , elucidating its importance for a more interactive and interesting educational scenario, leading to meaningful and participatory learning.